The Analysis of Factors that Influencing Investors Decision of Stock Investment in Batam - Dewi Khornida Marheni1 (YUME : Journal of Management, 2021)
AbstarctThe present study aims to seek the factors within an investor which can influence the stock investment decision in City of Batam with locus of control as a moderating variable. There are four variables used in this study, conservatism, availability, hearding, and overconfidence bias. Primary data were collected from online and offline by distributing questionnaire to investors in City of Batam. Total respondents in this study are 172 investors which are cleared from outlier. Then, the data were examined through SPSS version 25. Base on data analysis the result be concluded that variables of conservatism, availability, hearding, and overconfidence bias can affect positive  significantly towards investment decision making. Universitas Internasional BatamKeywords: Stock Investor, Investment Decision Making, Conservatism, Availability, Hearding, and Overconfidence bias